Effect of Different Cooking Methods on the Formation of Aroma Components and Heterocyclic Amines in Pork Loin. Issue 3 (7th July 2016) - Yang, Zhengmao; Lu, Rui; Song, Huanlu; Zhang, Yu; Tang, Jiani; Zhou, Ning
Abstract: The effect of three cooking methods on the formation of aroma components and heterocyclic amines in pork loin was investigated. The results illustrated that the content of heterocyclic amines in the electric oven‐cooked samples was higher than those in hot air fried and deep‐oil fried. The number of volatile compounds identified in the hot air fried and electric oven was similar. The aldehyde and pyrazine compounds were the key contributors to the aroma from high temperature heated meat. Three aroma compounds, hexanal, nonanal and benzaldehyde, were detected in all treated meat samples. This study is an initiative to detect and analyze the aroma components and heterocyclic amines from hot air fried pork loin and to obtain a basic understanding of flavor and safety of foods. Practical Applications: Diet is one of main factors that influence the health level of human. Pork is one of important animal‐derived foods for daily meal. Aroma components and potential hazards have been formed during different cooking methods. Heterocyclic amines (HAs) is one of mutagens can be formed in meat during heat treatment. This study is an initiative to detect and analyze the aroma components and heterocyclic amines from three different cooking methods, which obtain a basic understanding of flavor and safety of foods.